Taukil Wali Nikah Menurut KH. Ahmad Rifa’i dan Penerapannya di Kalangan Jama’ah Rifa’iyah Kecamatan Kesesi Kabupaten Pekalongan - Subhan, Abdul; Kholil, Makrum (Al-Hukkam: Journal of Islamic Family Law, 2021)
This paper examines the Taukil Guardian of Marriage According to KH. Ahmad Rifa'i and its application among the Rifa'iyah congregation, Kesesi District, Pekalongan Regency. Like what the opinion of KH. Ahmad Rifa'i about the marriage guardian taukil and how the implementation of the opinion of KH. Ahmad Rifa'i about the marriage guardian taukil among the Rifai'yah congregation, Kesesi District, Pekalongan Regency. The type of research carried out is library research, which is an effort to collect data by reading, studying books by KH. Ahmad Rifa'i and other books that have relevance to the preparation of this thesis, plus supporting data in the field. In the opinion of KH. Ahmad Rifa'i, when a woman does not have a marriage guardian, then she may tahkim, namely handing over her guardianship to someone who is 'alim' just to marry herself even though there is a judge. The figure of an 'alim' fair person is very important for someone who will become a marriage guardian. The judges who existed at the time of KH. Ahmad Rifa'i was judged to be a wicked person, because he was a stooge of the Dutch colonialists. Jama'ah Rifai'yah, Kesesi Subdistrict, Pekalongan Regency is still implementing the marriage contract with the tahkim guardian